International journal of epidemiology. - International Epidemiological Association (Oxford : Oxford University Press, 1972)
The International Journal of Epidemiology is an essential requirement for anyone who needs to keep up to date with epidemiological advances and new developments throughout the world. It encourages communication among those engaged in the research, teaching, and application of epidemiology of both communicable and non-communicable disease, including research into health services and medical care. Also covered are new methods, epidemiological and statistical, for the analysis of data used by those who practise social and preventive medicine.
"Published on behalf of The International Epidemiological Association"--Home page.
Description based on online resource; title from home page (viewed on September 28, 2016).
Keywords: Epidemiology -- Periodicals